Nanocomposite based on restacked crystallites of β-NiS and Ppy for the determination of theophylline and uric acid on screen-printed electrodes. (2nd December 2019) - Muthukumaran, P.; Ramya, R.; Thivya, P.; Wilson, J.; Ravi, G.
Abstract : We synthesized calcinated β-NiS with a highly crystalline porous nature and mixed it with Ppy to prepare a nanocomposite, which exhibited high electrocatalytic activity and this was then used to detect theophylline and uric acid with high sensitivity and stability. Abstract : Restacked nanosheets of nickel sulfide (β-NiS) and randomly attached polypyrrole (Ppy) nanospheres over a screen-printed electrode were demonstrated for the clinical evaluation of the simultaneous determination of theophylline (TP) and uric acid (UA). The impeded catalytic activity of β-NiS was revived by restacking using a calcination technique, which effectively enhanced the accessible surface area to improve the electrochemical performance. Then, the calcinated β-NiS-based hybrid nanocomposite exhibited excellent electrochemical activities for pharmaceutically important analytes, such as TP and UA simultaneously, in the range of 10 nM to 900 μM and 20 nM to 1 mM, with significant lowest detection limits of 1 nM and 5 nM. The practical utility of determining TP and UA present in human urine, serum, and fresh tea leaf extracts was successfully demonstrated with high selectivity and reproducibility. The experimental results exhibited that the porous crystalline β-NiS provides a promising platform for the rational design of sensors.